The Age And Paleoenvironment of The Pakaurangi Formation, Waitakere Group, Northland, New Zealand, Based on Ostracoda - Hasibuan, Fauzie; Hasibuan, A.R; Sudijono, Sudijono (Pusat Survei Geologi, 2006)
The Early Miocene Pakaurangi Formation, Waitakere Group, have a high diversity of Ostracoda. Key species include Loxoconcha propunctata, Bradleya semiarata, Bradleya lactea pakaurangia, Hemycythere tarakohensis and Bairdia canterburyensis, and indicate an Altonian age, completely in agreement with foraminiferal ages from this area by other workers.The species Trachyleberis zeacristata Hornibrook is transferred to Henryhowella. Paijenborchella iocosa Kingma, and many generic level taxa were also found in a borehole in Bojonegoro, East Jawa, Indonesia. The previously recorded Clifdenian to Waitotaran range of Henryhowella probesioides Hornibrook is extended downwards into the Altonian. The Ostracoda also show the paleoenvironment of the Pakaurangi Formation to be littoral to neritic, which is also in agreement with the evidence of foraminifera and molluscs as reported by previous workers. Keywords: Ostracoda, Pakaurangi Formation, Waitakere Group, Altonian, New Zealand